Pergeseran Penggunaan Bahasa Jawa di Kalangan Anak-Anak di Desa Sidoharjo Kabupaten Banyuasin - Ayu Puspita Indah Sari; Irvan Sururi (Jurnal Kajian Bahasa, Sastra dan Pengajaran (KIBASP), 2020)
The purpose of this study is to describe the incidence of the shift from Javanese to Indonesian among children in the village of Sidoharjo. The method used in this research is a qualitative research method that is carried out to describe or provide an actual picture of the process of the shift in Javanese language in Sidoharjo Village, Air Salek District, Banyuasin Regency. This research is focused on three domains in everyday life. These three domains include the family realm, the educational realm, and the religious realm. Based on the three domains, it is produced that the shift in the use of Javanese against Indonesian occurs in these three domains with the following percentages, in the family domain the shift in Javanese to Indonesian is 78%, in the environmental realm it is 65%, and in the religious realm it is 50% . In conclusion, there has been a shift in the use of Javanese towards Indonesian with a fairly high percentage of more than 50% among children in Sidoharjo village, Banyuasin district. Keywords: Language Shift, Javanese Language